Islamic Educational Pattern and Street Children Care - Hasan uddin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
This reseach aimed to determine the background of the emergence of street children stayed Puri Indah shelter house of Sidoarjo. In addition, this reseach also aimed to determine the pattern of communication that is formed, the steps of assistance and the factors driving and inhibiting the implementation of street child educational pattern. Qualitative descriptive research was done by collecting data using interviews, observation, literature study and documents. The informant was chosen by using purposive sampling. Analytical techniques used interactive analysis model which includes data collection, data reduction, data presentation and conclusion. From the research results could be seen that the cause of the emergence of street children because of economic factors, family disorganization, street family dynasties and customs tangent with street children. Responding to this Puri Indah shelter house of Sidoarjo made education pattern to street children. The communication pattern formed in this program is the formal communication seen at the time of routine learning and field study, non-formal communication seen in activity outside school and is more relaxed. Non verbal communication seen from the response of limbs of students. In connection with the interaction, there emerged a linear communication model, transactional and intransactional. The Puri Indah shelter house of Sidoarjo has innovative teaching methods both conducted by teachers and involving the active role of students. In order for our program to be more qualified, Puri Indah shelter house of Sidoarjo provided various facilities for students such as supporting books, bicycle, stationery library and paying attention to their nutrition. Nevertheless there was no doubt there were some weaknesses such as the arrogant nature of the students, the credibility of teachers who had not maximized, the limited facilities of infrastructure. However it could be overcome with the spirit of all elements and support of all parties. Keywords: Education, Parenting, Street Children